Partial albinism in Hawksbill turtle (Eretmochelys imbricata) in Rio Grande do Norte, Brazil - Rocha, Emanuel Lucas; Pinheiro da Silva, Lucas Gabriel Verissimo; Rocha Barreto, Isadora Nathalia; de Araújo Júnior, Hélio Noberto; Navoni, Julio Alejandro; de Oliveira, Moacir Franco; Bezerra de Moura, Carlos Eduardo (Universitas Airlangga, 2022)
Albinism is a genetic disorder in which there is a defect in melanin production, a pigment which gives color to the skin, hair and eyes. This congenital malformation can also occur in sea turtles, although it is not fatal, but it reduces their chances of survival in the natural environment. Even so, there are still no reports of its occurrence in Eretmochelys imbricata, a species known as the hawksbill turtle or legitimate turtle, with wide distribution in tropical seas. The present study describes the case of an individual with partial albinism in the E. imbricata species, found on the northern coast of Rio Grande do Norte, Brazil. The animals were collected at Cabo de Sí£o Roque beach in January 2020 during the reproductive season of the species. After analyzing the animal, it can be classified as having partial piebald albinism, since it still has lighter spots both on the skin and in the carapace and plastron regions.